2009
DOI: 10.1080/17470210802483545
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of conditioning of tentacle lowering in the snail (Helix aspersa)

Abstract: Experiment 1 established the effectiveness of an appetitive conditioning of odours procedure with snails (Helix aspersa) that was subsequently used for the study of blocking. In this important phenomenon, the conditioning of a CS1 (where CS is the conditioned stimulus) prior to conditioning of a compound, CS1CS2, blocked the conditioning to the CS2. Experiments 2a, 2b, and 2c demonstrated this associative effect using three different experimental controls. Experiments 3a and 3b replicated the blocking effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Of yet more interest, however, is recent work providing evidence of associative learning in invertebrate species. For example, demonstrations, not only of conditioning, but also of blocking, have been reported in insects [3], molluscs [4] and platyhelminthes [5].…”
Section: Case Study: Prosocial Behaviour In Chimpanzeesmentioning
confidence: 99%
“…Of yet more interest, however, is recent work providing evidence of associative learning in invertebrate species. For example, demonstrations, not only of conditioning, but also of blocking, have been reported in insects [3], molluscs [4] and platyhelminthes [5].…”
Section: Case Study: Prosocial Behaviour In Chimpanzeesmentioning
confidence: 99%
“…Cue competition effects have been observed in both appetitively and aversively motivated tasks, and across a wide range of invertebrate species including planaria (Prados et al, 2013), snails (Acebes et al, 2009), and honeybees (Couvillon & Bitterman, 1989), as well as vertebrates such as rodents (Kamin 1968), pigeons (Leyland & Mackintosh, 1978), non-human primates (Waelti, Dickinson & Schultz, 2001), and humans (Dickinson, Shanks & Evenden, 1984).…”
mentioning
confidence: 99%
“…that was located on the plastic tray by the snail. Previous research (Acebes et al, 2009;Loy et al, 2006) has demonstrated no differences in the CRs given to the different CSs at the beginning of a conditioning phase or in the course of conditioning when associated with the US. Despite this, the roles of the CSs (CS 1 -CS 2 ) were counterbalanced; we ran the experiment twice and merging the data in the analysis, as no significant differences were observed between them.…”
Section: Methodsmentioning
confidence: 99%
“…This is but one more step in an organized effort to replicate the relevant phenomena of associative learning in an invertebrate model (see Acebes et al, 2009;Loy et al, 2006;Ungless, 1998). This invertebrate model could be a useful instrument to use to further our understanding of the physiological bases of learning and memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation